Bibliometric Mapping of Risk Management Practices in High-Emission Industries - Loso Judijanto; Indah Oktari Wijayanti (Westscience Press, 2025)
High-emission industries play a pivotal role in economic development while simultaneously accounting for a disproportionate share of global greenhouse gas emissions. As these sectors face intensifying regulatory, financial, and societal pressure, risk management has expanded from a narrow focus on operational and safety issues toward broader environmental, climate, and sustainability risks. This study conducts a bibliometric mapping of research on risk management practices in high-emission industries using data retrieved from the Scopus database and analyzed with VOSviewer. Co-authorship, co-citation, and keyword co-occurrence networks are employed to identify influential authors, institutions, countries, thematic clusters, and temporal trends. The results show that “risk management” and “sustainable development” form the conceptual core of the field, closely linked to themes such as climate change, carbon emissions, emission control, environmental and health risks, and sector-specific concerns in construction and gas industries. Overlay and density visualizations indicate a shift from early work on air pollution, health risks, and environmental monitoring toward more recent emphasis on carbon accountability and climate-transition agendas. Country collaboration networks reveal a core group of leading contributors (particularly the United States, United Kingdom, China, and India) surrounded by emerging participants. Overall, the study consolidates a fragmented literature, clarifies the intellectual structure and evolution of the field, and highlights opportunities for future research on how risk management can support low-carbon transitions in carbon-intensive sectors.